Compositions featuring an attenuated Newcastle disease virus and methods of use for treating neoplasia - CARROLL DANIELLE; GALINSKI MARK; JIN HONG; MCCOURT MATTHEW; CHEN XING (2020)
The present invention provides methods for inducing regression of tumors in human subjects, the methods utilize a modified mesogenic strain of Newcastle disease virus (NDV) with modified F protein cleavage site, which is non-pathogenic to poultry (lentogenic), but exhibits oncolytic properties. The disclosed methods provide safe, effective and reliable means to induce regression of a tumor in an individual in need thereof. These methods overcome the drawbacks of using pathogenic strains of viruses for human therapy. 本发明涉及以减毒的新城疫病毒为特征的组合物和用于治疗瘤形成的使用方法。本发明提供了用于在人类受试者中诱导肿瘤消退的方法，这些方法利用具有修饰的F蛋白质切割位点的新城疫病毒（NDV）的修饰的中等毒力株，该中等毒力株对家禽是不致病的（弱毒力），但是展现出溶瘤特性。这些披露的方法提供了安全、有效和可靠的手段在对其需要的个体中诱导肿瘤消退。这些方法克服了使用病毒的致病株用于人类疗法的缺点。